1990
DOI: 10.1016/0016-6480(90)90080-6
|View full text |Cite
|
Sign up to set email alerts
|

Cultured pituitary cell GtH response to GnRH at different stages of rainbow trout spermatogenesis and influence of steroid hormones

Abstract: Using primary cultures of whole dispersed pituitary cells collected from rainbow trout at different stages of spermatogenesis, basal and GnRH-induced GtH release and cell GtH content were studied in control and steroid-pretreated cultures. Steroid pretreatments were performed for 3 days with 11-ketotestosterone (11KT) and 17 alpha-hydroxy,20 beta-dihydroprogesterone (17 alpha 20 beta p) at levels corresponding to those circulating at the time of spermiation (50 and 20 ng/ml, respectively). In control cultures,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…We suggest that this hormone may act on fish testis not only directly, but also indirectly through central feedback mechanisms, because the morphological features of GTH ce11 activation were obvious in androgen-treated males in Our experiments. These findings are in agreement with data obtained by many other investigators who has revealed stimulatory influence of exogenous androgens on brain aromatase activity, pituitary GTH cells' sensitivity to GnRH, as well as on GnRH, GTH and endogenous androgen production in salmonid males (van Overveek and McBride, 1971 ;Crim and Peter, 1978;Evans, 1979, 1983;Weil and Marcuzzi, 1990;Mayer et al, 1991;Amano et al, 1994). Furthermore, significant changes in testosterone binding in the brain were found in salmon males injected with "Testoenatum" (Christoforov and Murza,199 1 ).…”
Section: Discussionsupporting
confidence: 93%
“…We suggest that this hormone may act on fish testis not only directly, but also indirectly through central feedback mechanisms, because the morphological features of GTH ce11 activation were obvious in androgen-treated males in Our experiments. These findings are in agreement with data obtained by many other investigators who has revealed stimulatory influence of exogenous androgens on brain aromatase activity, pituitary GTH cells' sensitivity to GnRH, as well as on GnRH, GTH and endogenous androgen production in salmonid males (van Overveek and McBride, 1971 ;Crim and Peter, 1978;Evans, 1979, 1983;Weil and Marcuzzi, 1990;Mayer et al, 1991;Amano et al, 1994). Furthermore, significant changes in testosterone binding in the brain were found in salmon males injected with "Testoenatum" (Christoforov and Murza,199 1 ).…”
Section: Discussionsupporting
confidence: 93%
“…In teleosts, both T and 11‐KT can potentiate GnRH‐induced GtH release (Antonopoulou et al,1999; Borg,1994; Breton and Sambroni,1996; Lo and Chang,1998a,b; Weil and Marcuzzi,1990). The results presented here, together with a recent report that describes GnRH‐R1 but not GnRH‐R2 expression in the ventral pituitary of A. burtoni (Chen and Fernald,2006), suggest that the effect of androgen on GtH release at the level of the pituitary is potentially sensitive to influence by the GnRH‐R1 pathway in LH/FSH‐releasing gonadotropes.…”
Section: Discussionmentioning
confidence: 99%
“…As a potential role of the 17a201O0HP, D6peche and Sire (1982) proposed the regulation of spermatogonial multiplication and/or the activation of meiosis. The question whether 17a20POHP may play a role in the feedback regulation of the hypophysis remains in discussion: neither an effect of progestins on the concentration of GtH II in the hypophysis could be detected, nor on the secretion of GtH II by the hypophysis of immature fish (Crim et al 1981;Groves and Batten 1986), while other authors reported that 17a203OHP can modulate the response of hypophyseal cells obtained from mature male trout to GnRH (Weil and Marcuzzi 1990).…”
Section: Discussionmentioning
confidence: 94%